Biocompatability of hemodialysis membranes - Aksoy, M. Emin. (Thesis (M.S.) - Bogazici University. Institute of Biomedical Engineering, 1996., 1996)
With the development of biomaterials the term biocompatability was required to classify these materials in regard to their biological interaction. Biocompatability in extracorporeal blood treatments like hemodialysis is especially important, because all the pathways to bioincompatability become active, when the blood interacts with the membranes used for hemodialysis. The objective of this thesis was to have a better knowledge about the membranes used for hemodialysis and the blood-membrane interactions. In this study, stereomicroscopic evaluation, scanning electron microscopic (SEM) evaluation and tensile testing of the dialysis membranes have been performed. Besides these experiments, patient monitorisation and blood tests consisting of the determination of blood fibrinogen levels, complement 3 levels and white blood cell count during hemodialysis using four different membranes (Polysulfone, Cuprophan, Hemophan and Cellulose- diacetate). Depending on the experiments performed, it can be concluded that polysulfone membranes were the best ones in terms of biocompatability, while cellulose-acetate was the worst one.
Keywords: Membranes (Biology)